2020
DOI: 10.5946/ce.2019.065
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Dual Red Imaging in Gastric Endoscopic Submucosal Dissection: A Pilot Study

Abstract: Background/Aims: Dual red imaging (DRI) is a new, image-enhanced endoscopy technique. There are few reports about the usefulness of DRI during gastric endoscopic submucosal dissection (ESD). We aimed to examine the usefulness of DRI in endoscopic hemostasis during gastric ESD. Methods:We enrolled a total of 20 consecutive patients who underwent gastric ESD. Five endoscopists compared DRI with white light imaging (WLI) for the visibility of blood vessels and bleeding points while performing endoscopic hemostasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…DRI is useful in the presence of a spurting hemorrhage from a duodenal ulcer; bleeding point is noted as deep yellow, leading to clear identification of the bleeding point. 4 A retrospective study by Yorita et al 5 showed that DRI improved the visibility of blood vessels and bleeding points, especially in the presence of oozing blood and pooling of blood during gastric ESD. Maehata et al 6 studied the usefulness of DRI in visualizing bleeding points and hemostasis time during ESD.…”
Section: Discussionmentioning
confidence: 99%
“…DRI is useful in the presence of a spurting hemorrhage from a duodenal ulcer; bleeding point is noted as deep yellow, leading to clear identification of the bleeding point. 4 A retrospective study by Yorita et al 5 showed that DRI improved the visibility of blood vessels and bleeding points, especially in the presence of oozing blood and pooling of blood during gastric ESD. Maehata et al 6 studied the usefulness of DRI in visualizing bleeding points and hemostasis time during ESD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3–5 ] Comparing with clinical imaging modalities such as X‐ray, computed tomography (CT), magnetic resonance imaging (MRI), nuclear emission CT, and ultrasonography (US) which are able to visualize internal biological tissues/organs, endoscopic modalities provide more accurate local information with a high spatiotemporal resolution. [ 6–9 ] Table 1 presents the performances of different imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…provide more accurate local information with a high spatiotemporal resolution. [6][7][8][9] Table 1 presents the performances of different imaging techniques.…”
mentioning
confidence: 99%
“…RDI may reduce the stress experienced by endoscopists, allowing them to avoid vessels and treat bleeding quickly and effectively when it occurs. 3,4 Although it has been previously reported that RDI enables a shortened time to achieve hemostasis, 5,6 its usefulness in helping to prevent bleeding during all steps of ESD has yet to be clarified. In this ESD case, we demonstrated the benefits of full-time RDI, which included not only identifying bleeding points for quick and effective hemostasis but also preventing bleeding by avoiding deep vessels.…”
mentioning
confidence: 99%